KAJIAN KONSERVASI BANGUNAN CAGAR BUDAYA PADA KORIDOR JL. KEPODANG KOTA SEMARANG - Eko Anton Rubiantoro (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
The city of Semarang is rich in heritage objects. The existence of cultural heritage buildings in the Old City of Semarang for decades has suffered damage due to the age factor of buildings and natural factors such as: floods, rob and sea water intrusion and extreme weather. Another factor that causes damage or disappearance of cultural heritage buildings is to become a victim of development that is oriented to capital power. Learning from experience, the Semarang City Government has made several efforts to maintain the existence and existence of existing cultural heritage buildings. The effort was initiated by the issuance of Mayor Decree 650/50/1992 for 102 ancient or historic buildings in the city of Semarang that are worth protecting. Subsequently followed by the issuance of the Semarang City Regulation Number 16/2003 concerning the Old City Building and Environment Planning System. The Semarang City Government has collaborated with various elements of the community to make conservation efforts in several cultural heritage buildings in the Old City Region of Semarang. The type of conservation that is carried out as much as possible maintains the condition of the existing building forms, namely through preservation and restoration / rehabilitation. Conservation needs to be continuously improved through collaboration between the Government, Area Management Organizations, Building Owners and Investors. The Semarang City Government needs to continue to play an active role in conservation activities, especially related to policies and funding side.